2011
DOI: 10.1007/s00383-010-2843-7
|View full text |Cite
|
Sign up to set email alerts
|

The vacuum bell for conservative treatment of pectus excavatum: the Basle experience

Abstract: Objective Surgical repair of pectus excavatum (PE) in childhood is a well-established procedure. Previously used operative techniques to correct PE were largely based on the Ravitch technique. Since about 10 years, the minimally invasive repair (MIRPE) by Nuss is well established. Conservative treatment with the vacuum bell to elevate the funnel in patients with PE represents a potential alternative to surgery in selected patients. Methods A suction cup is used to create a vacuum at the anterior chest wall. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 21 publications
(30 reference statements)
1
44
0
1
Order By: Relevance
“…CT-scans showed that the device was able to lift the sternum and ribs immediately (17). Afterwards, several studies involving a larger pool of patients were done (19,20), and the first systematic review summarizing the results of 133 patients was published in 2011 (21). Furthermore, recent studies confirmed the efficacy of VB therapy in carefully selected patients (22)(23)(24).…”
Section: Introductionmentioning
confidence: 73%
“…CT-scans showed that the device was able to lift the sternum and ribs immediately (17). Afterwards, several studies involving a larger pool of patients were done (19,20), and the first systematic review summarizing the results of 133 patients was published in 2011 (21). Furthermore, recent studies confirmed the efficacy of VB therapy in carefully selected patients (22)(23)(24).…”
Section: Introductionmentioning
confidence: 73%
“…The most common complaints are shortness of breath with exercise, lack of endurance, and chest pain. If the patient has a mild deformity and does not fulfill the abovementioned criteria for surgical correction, then he/she will be started on a deep breathing with breath holding and posture exercise program, and may be offered non-operative treatment with the Vacuum Bell (19,20). These patients are typically re-evaluated every 3 to 6 months to ensure that they are complying with the conservative treatment and to check whether the deformity is improving or progressing.…”
Section: Pre-operative Evaluationmentioning
confidence: 99%
“…New approaches to the problem will also appear, as exemplified by Klobe's Vacuum Bell, which is now finding a place as the treatment of choice in younger patients with a soft and malleable chest who have a mild to moderate deformity (19,20). At one time there was only one procedure available for patients with pectus excavatum and that was the Ravitch procedure.…”
Section: Futurementioning
confidence: 99%
“…More recently these patients have been offered treatment with the Vacuum Bell (19,20) The advent of the MIRPE resulted in a dramatic increase in the number of patients presenting for repair (15,21). This large increase in the numbers of patients undergoing repair has allowed many centers to develop technical refinements, thereby making the procedure even safer and has allowed numerous pre-and post-operative studies to be performed, showing that pectus excavatum causes significant cardiac and pulmonary compression and dysfunction which is markedly improved after repair (22)(23)(24).…”
Section: Surgical Indicationsmentioning
confidence: 99%